2003
DOI: 10.1542/peds.112.2.332
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Course of Infantile Pompe’s Disease: 20 Original Cases Compared With 133 Cases From the Literature

Abstract: Survival, decrease of the diastolic thickness of the left ventricular posterior wall, and achievement of major motor milestones are valid endpoints for therapeutic studies of infantile Pompe's disease. Mutation analysis and measurement of the alpha-glucosidase activity should be part of the enrollment program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
368
1
12

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 480 publications
(387 citation statements)
references
References 82 publications
6
368
1
12
Order By: Relevance
“…In both studies, cardiomegaly, cardiomyopathy, hypotonia, muscle weakness, respiratory distress, respiratory infections, feeding difficulties, and failure to thrive were reported as frequently presenting signs and symptoms 5,6,18. In summary, both studies concluded that the natural history of infantile Pompe disease has changed little since its original description, though the absence of large, well characterized and unbiased data sets has been a limitation.…”
Section: General/backgroundmentioning
confidence: 93%
See 3 more Smart Citations
“…In both studies, cardiomegaly, cardiomyopathy, hypotonia, muscle weakness, respiratory distress, respiratory infections, feeding difficulties, and failure to thrive were reported as frequently presenting signs and symptoms 5,6,18. In summary, both studies concluded that the natural history of infantile Pompe disease has changed little since its original description, though the absence of large, well characterized and unbiased data sets has been a limitation.…”
Section: General/backgroundmentioning
confidence: 93%
“…Herein, we have considered Pompe disease a continuum of disease spectrum varying by age of onset, organ involvement and degree of myopathy. In an attempt towards establishing a uniform terminology, we broadly classify Pompe disease as follows: infantile form that includespatients as originally described by PJ Pompe, a Dutch pathologist, in 19324 who exhibit rapidly progressive disease characterized by prominent cardiomegaly, hepatomegaly, weakness and hypotonia, and death due to cardiorespiratory failure in the first year 5,6. This represents the most severe end of the disease spectrum and is often referred to as classic infantile Pompe disease.…”
Section: General/backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…The cardinal features of severe cardiomyopathy and muscle weakness represent the phenotype of infantile Pompe disease, with prediction of death at a median age of 7.7 and 6 months in Dutch and non-Dutch patients, respectively (Van den Hout et al 2003) . Kishnani et al reported on the impact of rhGAA on prolonging the survival of infants with Pompe disease (Kishnani et al 2009), while Kanters et al have demonstrated the substantial burden of disease both on the individual and the society in adults with Pompe disease (Kanters et al 2011).…”
Section: Introductionmentioning
confidence: 99%